Comparison of preoperative infraorbital block with peri-incisional infiltration for postoperative pain relief in cleft lip surgeries - Gaonkar, V.; Daftary, Swati R. (Indian Journal of Plastic Surgery, 2004)
In this prospective, randomized study, children undergoing cleft lip surgery were either given infra-orbital nerve block (n=25) or peri-incisional infiltration (n=25) pre-operatively with 0.25% bupivacaine in 1:2,00,000 adrenaline.The overall course of anesthesia in both the groups was smooth, with excellent hemodynamic stability, indicating better pain relief during the intra-operative period. The concentration of the anesthetic agent required was reduced and recovery from anesthesia was rapid and complete. There was excellent postoperative analgesia. The children were calm and comfortable postoperatively.We conclude that infra-orbital nerve block with 0.25% bupivacaine with adrenaline provides more prolonged analgesia than peri-incisional infiltration in cleft lip repair. Infra-orbital block given by modified approach is easy to perform and free of side-effects.
Keywords: Surgery: Cleft lip; Pain relief: Infraorbital block; peri-incisional infiltration